Formação profissional e mercado de trabalho: um estudo da Petrobrás por meio das empresas prestadoras de serviços da cidade de Mossoró (RN) - Oliveira, Neófita Maria de (2011)
We have seen gradually from the 1980s, replacing the model of organization of work processes based on mass production (Taylorismo / Fordismo) through model for flexible manufacturing (Toyota). Due to these changes, there is a strong demand for innovative enterprises by workers with a professional attitude associated with sensitivity to the visionary eye and natural predisposition towards their learning. Understanding this reality is our intention in this study, having as the problematic inclusion of youth in the labor market in the city of Mossoró (RN), seeking to understand if the professional training and technology of youngsters, egress from IFRN and SENAI meet market requirements work, leading them to compete vigorously and with chances of employment within various geographic locations. One segment that stood out in the productive process of Mossoró (RN) and the region was the increasing oil activity, which has become a raw material of major importance to the economic development of Brazil and local, ensuring the facilities of oil exploration, natural gas and has contributed significantly to oil exploration companies and services provided to Petrobrás were installed in Mossoró, including multinationals such as Schlumberger and Halliburton that are companies seeking highly qualified professionals to act on them. These facilities collaborated to create new businesses in the region and expanded the conditions for insertion in the employment of young graduates of IFRN and SENAI. The analysis of this problem will be effective to a study consisting of semi-structured interviews with the public that belong in the list of employees graduates in the IFRN and SENAI, students, teachers and principals of the selected companies. We hope reaffirm our hypothesis and to progress on further study of the Work Sociology in the field of professional qualification in the globalized labor world. We will have in the studies developed by Marx, Braverman, Coriat, Friedmann, Naville and Zarifian the theoretical basis of our investigations. Besides studies of national authors who have developed significant research on the proposed theme